Super facile one-step synthesis of aromatic amine waste residue derived N-rich porous carbon for hyper efficient p-nitrophenol adsorption. Issue 2 (April 2021) - Ding, Junwei; Li, Xin; Shan, Yuling; Yu, Shitao; Yu, Wenlong; Liu, Yibin; Zhao, Wenting; Li, Xiaoke; Liu, Mengxiao; Ding, Yuqi
Abstract: Both nitrophenol wastewater and aromatic amine industrial waste residue are serious threats to our environment. In this paper, N-rich porous carbons (NPC) derived from industrial aromatic amine waste residue were prepared via a facile "carbonization-activation" one-step approach. Owing to the extremely high activation efficiency of amine residue-NaOH matching strategy, NPC prepared with 1.5 of NaOH-residue ratio obtained an ultra-high specific surface area of 3120 m 2 /g with a huge pore volume of 2.381 cm 3 /g. XPS analysis shows that graphitic-N and pyridinic-N are the main N-doped species. The plentiful pore structure, ultra-high surface area, and modification of nitrogen-doped sites rendered the NPCs remarkable adsorption capacity (1030.51 mg/g) for p-nitrophenol (PNP). Adsorption isotherms and adsorption kinetics indicated the adsorption behavior of PNP molecules on NPCs surface adhered to the mechanism of monolayer adsorption and pseudo-second-order kinetic. DFT calculation studies revealed that N-doped species could effectively enhance the adsorption energy of PNP on carbon surface due to the enhanced dispersion and electrostatic attraction. Particularly, the pyridinic-N made an outstanding contribution to improve the interactions through hydrogen bonding. Furthermore, the NPC-1.5 showed an excellent adsorption stability for PNP in the reusability test of 12 cycles, reflecting its great potential in practical application. Graphical Abstract: ga1 Highlights: N-rich porous carbons (NPCs) derived from amine industrial residue were prepared. A "pyrolysis-activation" one-step strategy gave the NPC an ultrahigh surface area. NPCs were used for p-nitrophenol (PNP) removal with super-high adsorption capacity. The key roles of N-species were illuminated via experimental and DFT methods. Enhanced adsorption of PNP can be explained by dispersion and electrostatics.